Production of Exopolysaccharides by Strains of Streptococcus thermophilus - UMI PURWANDARI; TODOR VASILJEVIC (Microbiology Indonesia, 2010)
Two strains of Streptococcus thermophilus producing capsular and capsular-ropy exopolysaccharides (EPS) were examined for their growth and EPS production in M17 medium supplemented with glucose, galactose or lactose and incubated at 30, 37 or 42°C for 24 hours. Growth parameters (viable cells, OD, lactate production, pH) and EPS production were determined. Flow behavior of the EPS dispersions was assessed as a function of concentration and temperature. Culture growth during incubation was affected by types of sugar, temperature and time. Growth was enhanced by glucose, lactose and higher incubation temperature. EPS concentration in the medium was greater in the presence of glucose and galactose. Despite the restricted growth conditions, the capsular strain produced comparable levels of EPS to the capsular-ropy strain even under sub-optimal incubation temperature